Combinatorial methods for testing Internet of Things smart home systems. (28th December 2021) - Garn, Bernhard; Schreiber, Dominik‐Philip; Simos, Dimitris E.; Kuhn, Rick; Voas, Jeff; Kacker, Raghu
Summary: In this paper, we report on applying combinatorial testing to Internet of Things (IoT) home automation hub systems. We detail how to create a dedicated input parameter model of an IoT home automation hub system for use with combinatorial test case generation strategies. Further, we developed an automated test execution framework and two test oracles for evaluation purposes. We applied and evaluated our proposed methodological approach to a real‐world IoT system and analysed the obtained results of various combinatorial test sets with different properties generated based on the derived input model. Additionally, we compare these results to a random testing approach. Our empirical testing evaluations revealed multiple errors in the tested devices and also showed that all considered approaches performed nearly equally well. Abstract : The graphical abstract depicts a combinatorial methodology for testing Internet of Things systems in the case of a hub‐based home automation system represented as a star graph.